Origins of Farmers’ Adoption of Multiple Climate-Smart Agriculture Management Practices in the Vietnamese Mekong Delta - Luu, Dung Tien (UI Scholars Hub, 2020)
Farmers’ adoption of multiple climate-smart agricultural practices may guarantee food security and economic and social efficiency considering the adverse effects of climate change. This study investigates the adoption of climate-smart agricultural technologies among farmers in the Mekong Delta, Vietnam. The analysis used a primary data sample of 350 rice farmers and a multinomial logit model. The findings indicate that the most critical determinants of climate-smart agricultural technology adoption among farmers include perceived impact of climate change, farmer’s education level, farm size, access to credit, social capital, access to extension, secured farmland tenure, and constraint to market. The results demonstrate the need for policymaking designed to improve the probability of households applying climate-smart agricultural technology as the most crucial step in successfully implementing adaptive agricultural production strategies to climate change.